From uncertainty to ambiguity: A discursive approach of emerging field - Zong, Zhen; Demil, Benoît (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2015)
Emerging fields offer an opportunity to study how actors are making sense of their environment. In this article, we adopt a discursive approach to examine the discourses about uncertainty. These discourses produced by state and non-state actors are particularly interesting as they participate in the emergence of the institutional framework. We study the discourses produced during a public inquiry led in 2009 and 2010 in the nascent French nanotech field to observe the use of discourses to influence understandings and meanings. We found that ambiguity is used differently according to the positions of actors in the field and that the rhetoric of uncertainty targets different goals.